Treatment of Axillary Osmidrosis Using a Subcutaneous Pulsed Nd-YAG Laser - Daejin Kim; Junhyung Kim; Hyeonjung Yeo; Hyukjun Kwon; Daegu Son; Kihwan Han (Archives of Plastic Surgery, 2012)
Background Axillary osmidrosis is characterized by an unpleasant odor, profuse sweating, and in some instances, staining of clothes that may socially and psychologically impair affected individuals. Various types of surgical procedures have been developed for the treatment of axillary osmidrosis. This study was undertaken to evaluate the effectiveness of subcutaneous pulsed neodymium: yttrium-aluminum-garnet (Nd-YAG) laser treatment for the treatment of axillary osmidrosis. Methods Twenty-nine patients with axillary osmidrosis were included in this study. Patients were categorized according to the results of an axillary malodor grading system, and a subcutaneous pulsed Nd-YAG laser was applied to all patients. The treatment area for the appropriate distribution of laser energy was determined using the iodine starch test (Minor's test) against a grid pattern composed of 2×2 cm squares. The endpoint of exposure was 300 to 500 J for each grid, depending on the preoperative evaluation results. The results were evaluated by measurement of axillary malodor both pre- and postoperatively using the grading system and iodine starch test. Results The average follow-up period was 12.8 months. Nineteen patients had a fair-to-good result and ten patients had poor results. The postoperative Minor's test demonstrated that there were remarkable improvements for patients with mild to moderate symptoms. Complications including superficial second degree burns (n=3) were treated in a conservative manner. A deep second degree burn (n=1) was treated by a surgical procedure. Conclusions Subcutaneous pulsed Nd-YAG laser has many advantages and is an effective noninvasive treatment for mild to moderate axillary osmidrosis.